Particulate Matter as a Driven Factor Covid19 Transmission at Outdoor: Review - Hanien Firmansyah; Azmi Nur Fadlillah; Aditya Sukma Pawitra (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: Coronavirus Disease 2019 (Covid19) is an infectious disease caused by SARS-CoV-2 (Severe Acute Respiratory Syndrome-related Coronavirus) which attacks the respiratory tract, with mild to severe symptoms. The virus can infect the body through mucous membranes on the face with droplet transmission. Air pollution is thought to contribute to Covid19 events which can worsen the situation of people with Covid19. The aims of this literature review is to analyze Particulate Matter (PM) as environmental factors that contributes Covid19, so it is expected to be a study in terms of prevention and prevention in the field of environmental health. Discussion: PM is thought to have contributed to an increased risk of mortality and morbidity in Covid19 events. PM which has toxic properties can enter the lungs and affect the physiological condition of the lung organs. The findings regarding the presence of SARS-CoV-2 virus RNA strengthen the suspicion that PM plays a role in Covid19 transmission. Several studies have found that there is a relationship between PM and Covid19. PM2.5 which is smaller than PM10 has a higher ability to be a risk factor for ballast in Covid19. Conclusion: The results of this synthesis state that PM can be one of the driving factors of Covid19 transmission in air.